Uso de chatbot para pré-triagem: um estudo de caso em clínica odontológica universitária - VIDAL, Douglas Almeida (2022)
Chatbots or conversational agents tools have become catalysts for the media, especially with the needs arising from COVID-19 and the increase in artificial intelligence (AI) solutions. Faced with a problem in the health area, the present work presents a case study of the use of chatbots, specifically the WhatsApp messaging application, to assist in the pre-screening sector of a university dental clinic with structural and organizational problems. To this end, several chatbot solutions were compared and the DialogFlow tool was chosen, which uses Machine Learning techniques to create the chatbot and the Twillio cloud communication platform, to make the connection with the social network, using natural processing. of language. To obtain the results, contact tests were applied, which analyze the bot's responsiveness and possible failures. The results indicate that the chatbot solution can assist in the screening of patients and usability tests were applied, with a sample space of 15 users, using the PSSUQ questionnaire model. The results point to good usability, as 92% of the questionnaire items received values above 6 (values range from 1 to 7), revealing the good functioning and good acceptance of the chatbot by end users.